Adverbs eding in -LY in late modern english. Evidence form the Coruña corpus of history english texts. Núm 4 - Álvarez Gil, Francisco José (Estudios de lingüística aplicada, 2019)
The objective of the present study is to analyse the meaning and function of -ly adverbs in the scientific register, specifically in history texts, across the eighteenth and nineteenth centuries, known as well as the Late Modern Period.The sample analysed is from the Corpus of History English Texts (CHET) one of the subcorpus of the Coruña Corpus of English Scientific Writing.The selection of those centuries is not fortuitous as this period of the language is essential in the development of the scientific register as we know it nowadays.